2019
DOI: 10.1080/09692290.2019.1567571
|View full text |Cite
|
Sign up to set email alerts
|

All exclusive: the politics of offshore finance in Mexico

Abstract: At first sight, Mexico appears to be a textbook example of a state affected by offshore finance. Offshore financial services allow corporations and the wealthy to plan taxes, avoid regulations or to launder money. The literature holds that large, developing, open economies, with geographical proximity to offshore centers and problems of crime and corruption are particularly affected by offshoring. By this logic, we should expect Mexico to show a significant demand for offshore financial services. Yet, new empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…The Mayan Riviera is also at risk for money laundering given that it is the main gateway for international tourists into Mexico and given the country's relatively weak border controls (IMF, 2017). Overall, this paper concurs with Binder (Binder, 2019) in affirming that Mexico, despite its geographical proximity to offshore tax havens (i.e. Belize), can provide "formidable spaces for onshore money laundering."…”
Section: Trcsupporting
confidence: 75%
“…The Mayan Riviera is also at risk for money laundering given that it is the main gateway for international tourists into Mexico and given the country's relatively weak border controls (IMF, 2017). Overall, this paper concurs with Binder (Binder, 2019) in affirming that Mexico, despite its geographical proximity to offshore tax havens (i.e. Belize), can provide "formidable spaces for onshore money laundering."…”
Section: Trcsupporting
confidence: 75%
“…Somewhat paradoxically, little is known about the evolution of the Eurodollar market since the 1980sthe topic all but disappeared from the IPE literature precisely when the Eurodollar market had become the backbone of the international monetary and financial system. Recent research, however, has shown that it is impossible to make sense of financial globalization and US monetary power without a thorough understanding of the offshore dollar system (Binder, 2019;Hardie & Maxfield, 2016;Hardie and Thompson, forthcoming;Murau, 2018;Schwartz, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…First, weak institutions make it easier for political and business groups to infiltrate the policymaking process and evade capital controls (Kang, 2002;Méon and Sekkat, 2005;Aleksynska and Havrylchyk, 2013). Furthermore, institutional weaknesses form a comfortable breeding ground for all sorts of criminal activities (Bruno, 2019), effectively functioning as a trigger for investors to deposit their profits in offshore accounts for safekeeping (Hessami, 2014;Binder, 2019). An empirical implication is that elite capital flight should be more pronounced in countries with relatively closed capital accounts.…”
Section: Background and Hypothesesmentioning
confidence: 99%